ANALISIS PENYEBAB ANAK PUTUS SEKOLAH PADA JENJANG PENDIDIKAN DASAR DI DESA ENGKURAI - Marta, Julita Kristiani; Nugraha, Asep Eka; Anggorowati, Kurnia Dyah (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2023)
This study aims to analyze the causes of out-of-school children at the basic education level in Desa Engkurai, Kecamatan Pinoh Utara, Kabupaten Melawi. The subjects in this study are out-of-school children and parents of out-of-school children, the object of this study is the cause of out-of-school children at the basic education level. This research uses qualitative methods, qualitative approaches, the type of research is descriptive-qualitative. The instrument in this study uses interview sheets, then data collection techniques in this study use interviews and documentation, data analysis in this study is data collection, data reduction, data presentation and conclusions. While the validity test of the data used is triangulation of data sources. The results showed that the cause of children dropping out of school at the basic education level in Desa Engkurai, Kecamatan Pinoh Utara, Kabupaten Melawi was due to low interest in learning and schooling due to not mastering or understanding the material, not fluent in reading, not moving up in class, health factors, and the influence of poor treatment from the family. In addition, the child's thinking ability is still below average, as well as the sense of laziness that has been inherent in the child. Then the influence of the environment where the dropout child lives itself.